2022
DOI: 10.1016/j.xcrm.2021.100503
|View full text |Cite
|
Sign up to set email alerts
|

Making safe sense of an anti-sense!

Abstract: Bepiroversen has been developed and trialed for the cure of HBV. Yuen et al. 1 report on the safety and antiviral efficacy of this agent. We “spotlight” key findings of this study and its impact for future clinical trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…This stands in contrast to previous reports describing that in HBeAg‐positive NUC‐treated patients, ALT flares occur first and are then followed by HBsAg decline 59 . Currently, a phase II clinical trial aims to study the timing and mechanisms behind these ALT flares, by characterizing liver‐resident immune cells from patients treated with bepirovirsen (NCT04544956) 60 …”
Section: New Compounds Targeting Hbv As An Indirect Approach Against Hdvmentioning
confidence: 84%
See 1 more Smart Citation
“…This stands in contrast to previous reports describing that in HBeAg‐positive NUC‐treated patients, ALT flares occur first and are then followed by HBsAg decline 59 . Currently, a phase II clinical trial aims to study the timing and mechanisms behind these ALT flares, by characterizing liver‐resident immune cells from patients treated with bepirovirsen (NCT04544956) 60 …”
Section: New Compounds Targeting Hbv As An Indirect Approach Against Hdvmentioning
confidence: 84%
“…59 Currently, a phase II clinical trial aims to study the timing and mechanisms behind these ALT flares, by characterizing liver-resident immune cells from patients treated with bepirovirsen (NCT04544956). 60 The second molecule in this category is RO7062931, a GalNAcconjugated locked nucleic acid (LNA)-containing ASO, which has recently completed a phase I clinical trial to evaluate its safety and potential antiviral effect (NCT03038113). This study reported RO7062931 to be safe and well tolerated after 4 weeks of treatment.…”
Section: Targeting Hbv Gene Expressionmentioning
confidence: 99%